Regulating belonging: surveillance, inequality, and the cultural production of abjection. Issue 2 (4th March 2017) - Monahan, Torin
ABSTRACT: Conditions of abjection are increasingly viewed as problems to be managed with surveillance. Across disparate domains, bodies that challenge normalized constructions of responsible neoliberal citizenship are categorized, monitored, policed, and excluded in dehumanizing and often violent ways. This paper explores the role of surveillance in such processes. The registers covered include everyday abjection (welfare systems, battered women's shelters, and homelessness), criminalized poverty (police targeting of the poor and emerging 'poverty capitalism' arrangements), and the radically adrift (the identification, tracking, and containment of refugees). In each of these cases, surveillance is yoked to structural inequalities and systems of oppression, but it also possesses a cultural dimension that thrusts marginalized and dehumanized subjectivities upon the abject Other. Therefore, I argue that in order to critique the gendered, racialized, and classed dimensions of contemporary surveillance, it is necessary to take seriously the mythologies that give meaning to surveillance practices and the subjectivities that are engendered by them.